Arctic and northern community governance: The need for local planning and design as resilience strategy. (June 2022) - Van Assche, Kristof; Birchall, Jeff; Gruezmacher, Monica
Abstract: Northern regions are still less visible than others. This means that dealing with problems of the North often takes place in the mode of damage control. Drawing on Canadian and Alaskan experiences, we argue that northern communities need integrated resilience strategies for their development and that such strategies need to have the character of local plans. We argue therefore for local planning as a site of policy integration in the formulation of resilience strategy. A redefinition or reorientation of key terms is required however, with resilience taking on local attributes, planning understood as pro-active local design and governance seen as an always local northern bricolage. This approach can enhance the capacity to entertain alternative futures in the governance system, the capacity to assess constantly shifting problematizations of issues, and a better matching of locally desirable futures and existing assets. Highlights: Northern communities face problems requiring resilience strategy. Northern governance has features rendering this difficult. Local spatial planning provides an arena for strategy formation. Northern planning needs to deploy environmental design perspectives. Planning and design can enhance rather than reduce adaptive capacity.